Upaya Promotif Pencegahan Stunting melalui Edukasi Gizi Seimbang - Norhasanah, Norhasanah; Suryani, Nany (Universitas Baiturrahim, 2025)
Implementing balanced nutrition to prevent stunting is very necessary, considering that there is a very close relationship between intake and nutritional status. Nutritional status is directly related to nutritional intake and also infectious diseases. Implementing balanced nutrition in the family can begin with good nutritional knowledge from parents, especially mothers. This nutritional knowledge is very important in determining healthy and balanced food intake for families, including babies and toddlers. The low level of nutritional knowledge among parents and the negative impacts it causes are one of the reasons for the need to provide nutritional education regarding balanced nutrition. Balanced nutrition needs to be implemented from pre-conception until the child is two years old, especially for optimal growth and development. The application of balanced nutrition also needs to be applied to all other family members, because balanced nutrition is important in all life cycles. The activities carried out are in the form of nutrition education which are expected to increase nutritional knowledge among parents of children at PAUD Terpadu Sabila. Activity evaluation is carried out by comparing nutritional knowledge between before and after being given nutrition education. The results of the activity showed that there was a change in the nutrition knowledge of the child's parents when compared before and after nutrition education. The percentage of knowledge in the good category before the nutrition education was given was 51%, increasing to 100% after the nutrition education was given.